Cumacea from the continental shelf of Angola and Namibia with descriptions of new species - Bochert, Ralf; Zettler, Michael L. (Zootaxa, 2011)
During two sampling campaigns carried out in 2004 and 2008 on the shelf off Angola and northern Namibia (South West Africa), sixteen cumacean species belonging to the families Bodotriidae, Diastylidae and Pseudocumatidae were collected. Two of them are new to science, namely Bodotria fionae and Heterocuma ambrizetensis. Figures are drawn for the new species and additional for seven species, which are partially described up to date. Additionally, an adapted key to the species of Heterocuma is provided. Taxonomic and morphological features were analysed and the findings were compared and discussed with earlier investigations from West Africa.